The Impact of Innovations on the Business Model: Exploratory Analysis of a Small Travel Agency. (7th June 2016) - Rusu, Bogdan
Abstract: The objective of this exploratory paper is to analyse the innovations introduced by a small travel agency and their impact on the firm's business model in the specific context of a salt mine in Romania. In particular, the purpose of this paper is to analyse the business model of the small firm that did not introduce a single innovation. A case study provides rich data on "unbundling" made by the entrepreneur and the trade-offs decisions that affect the business model. The paper highlights the implications of the entrepreneur's decision to implement in a short period of time a "package" of product, process, marketing and organizational innovations and their impact upon the business model, and describes the transformation of the company due to changes in the environment (content and relationships among the building blocks of the business model).